Adaptive reversible data hiding algorithm for interpolated images using sorting and coding. (May 2022) - Xiong, Xiangguang; Chen, Yi; Fan, Mengting; Zhong, Siyao
Abstract: Existing reversible data hiding (RDH) algorithms based on the interpolation technology (IT) have high embedding capacities and visual qualities. However, they usually embed secret data directly into interpolated pixels sequentially, resulting in that the visual qualities may not be optimal. To address this problem, an adaptive IT-based RDH algorithm is proposed. First, for a given interpolated image, the amount of data that can be embedded into each interpolated pixel is sorted in the ascending order. Next, the secret data to be embedded are recoded and sequentially embedded into interpolated pixels after overflow/underflow preprocessing based on the obtained index. The experimental results demonstrate that the proposed algorithm outperforms several state-of-the-art RDH algorithms based on IT. On average, the average peak signal-to-noise ratio (PSNR) of our algorithm is improved by approximately 25%. In comparison with traditional RDH algorithms using histogram shifting and pixel value ordering, our algorithm also achieves a higher PSNR. In addition, our algorithm can resist histogram and regular singular steganalysis attacks. These results clearly demonstrate that the proposed algorithm is effective.